2016
DOI: 10.3201/eid2212.160382
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of MERS-CoV Infection and Immunity in Dromedary Camels

Abstract: Knowledge about immunity to Middle East respiratory syndrome coronavirus (MERS-CoV) in dromedary camels is essential for infection control and vaccination. A longitudinal study of 11 dam–calf pairs showed that calves lose maternal MERS-CoV antibodies 5–6 months postparturition and are left susceptible to infection, indicating a short window of opportunity for vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 15 publications
4
55
2
Order By: Relevance
“…We found 10 longitudinal studies describing 9 incidences of natural infection on farms and in quarantine facilities -1 in Egypt (Ali et al, 2017b), 4 in KSA (Azhar et al, 2014;Hemida et al, 2014a;Memish et al, 2014;Hemida et al, 2017a), 5 in UAE (Al Hammadi et al, 2015;Wernery et al, 2015a;Meyer et al, 2016;Muhairi et al, 2016;Yusof et al, 2017) and 1 study taking monthly samples of 430 dromedaries in Kenya (Kiambi et al, 2018).…”
Section: Evidence Of Infection and Immunity From Longitudinal Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…We found 10 longitudinal studies describing 9 incidences of natural infection on farms and in quarantine facilities -1 in Egypt (Ali et al, 2017b), 4 in KSA (Azhar et al, 2014;Hemida et al, 2014a;Memish et al, 2014;Hemida et al, 2017a), 5 in UAE (Al Hammadi et al, 2015;Wernery et al, 2015a;Meyer et al, 2016;Muhairi et al, 2016;Yusof et al, 2017) and 1 study taking monthly samples of 430 dromedaries in Kenya (Kiambi et al, 2018).…”
Section: Evidence Of Infection and Immunity From Longitudinal Studiesmentioning
confidence: 99%
“…Three studies have found dromedaries to be shedding MERS-CoV RNA despite having high antibody titres months or weeks prior to detectable infection. Both older animals whose antibodies reflect past exposure (Meyer et al, 2016;Ali et al, 2017b;Hemida et al, 2017a), and young calves whose high antibody titres were maternally-acquired immediately post-partum, became infected (Meyer et al, 2016).…”
Section: Evidence Of Reinfectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental challenge and transmission studies provided key data regarding the time course of infection. Field studies have also provided valuable information, including evidence supporting the duration of pathogen shedding (Al Muhairi et al, ), and documenting transmission among dromedaries (Ali, Shehata, et al, ; Meyer et al, ).…”
Section: Discussionmentioning
confidence: 99%